1982
DOI: 10.1083/jcb.94.2.444
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic models of viscous coupling between motile myosin and endoplasm in characean algae.

Abstract: Cytoplasmic streaming in characean algae is thought to be driven by interaction between stationary subcortical actin bundles and motile endoplasmic myosin. Implicit in this mechanism is a requirement for some form of coupling to transfer motive force from the moving myosin to the endoplasm. Three models of viscous coupling between myosin and endoplasm are presented here, and the hydrodynamic feasibility of each model is analyzed. The results show that individual myosinlike molecules moving along the actin bund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
3

Year Published

1983
1983
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 34 publications
4
32
3
Order By: Relevance
“…In this study, we assumed that cortical myosin generates a shear force against the cytoplasm to drive cytoplasmic streaming, as considered for characean algae (36). If this assumption were correct, the speed of the anterior-directed cortical myosin should be equal to that of materials just beneath the cell cortex, and this is the case for streaming in the C. elegans embryo (9).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we assumed that cortical myosin generates a shear force against the cytoplasm to drive cytoplasmic streaming, as considered for characean algae (36). If this assumption were correct, the speed of the anterior-directed cortical myosin should be equal to that of materials just beneath the cell cortex, and this is the case for streaming in the C. elegans embryo (9).…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of plant myosin had begun from attempting to elucidate the molecular mechanism of characeancytoplasmic streaming. The hydrodynamic analysis had proposed that only movement of long carling filamentous [125] or membrane network organelles expanding into the whole cytoplasm [66] could generate the motive force for the cytoplasmic streaming from actin cable to the viscous cytoplasm in characean cells, about 0.7-2 poise compared with 0.01 poise in a water. These organelles have been considered to be ER [38].…”
Section: Cytoplasmic Streaming In Characean Cellsmentioning
confidence: 99%
“…It is not so hard to imagine that cytoplasmic streaming is generated by myosin-like motor proteins which move on the actin bundles. Hydrodynamic considerations suggested that the myosin should move either with an attached membrane vesicle or endoplasmic reticulum to produce bulk streaming [12]. Figure 3 illustrates schematically the geometrical relationship between the chloroplasts, the actin bundles, plant myosins and membrane vesicles in characean cells.…”
mentioning
confidence: 99%